Control y represión. Estudio comparado de los resultados de la depuración del magisterio primario en España - Ramos Zamora, Sara (Revista Complutense de Educación, 2006)
The purge of the teachers training was one of the most repressive performances of the politics of the Franco’s government. The formation that teachers received during the II Republic, based on some modern cultural and pedagogical principles, on some currents of liberal thought, together with the application that they had to carry out of the republican educational model, favored that they were considered professionals spoiled by the Republic, contaminated of its ideals, and for that reason it was necessary to purify it. Along this article the author analyzes the obtained results in the case of the region of Castilla-La Mancha, comparing this geographic zone with other regions and provinces of Spain studied by other authors.